Sinapic acid attenuates cisplatin-induced nephrotoxicity through peroxisome proliferator-activated receptor gamma agonism in rats - Hardevinder Pal Singh; Thakur Gurjeet Singh; Randhir Singh (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to investigate the involvement of peroxisome proliferator-activated receptor gamma (PPAR-γ) in renal protection offered by sinapic acid in cisplatin-induced nephrotoxicity in male rats. Materials and Methods: Nephrotoxicity was induced by single dose of cisplatin (5 mg/kg, intraperitoneal [i.p.]) in rats. Cisplatin-induced nephrotoxicity was assessed by measuring serum creatinine, creatinine clearance, urea, uric acid, potassium, magnesium levels, fractional excretion of sodium, and microproteinuria in rats. Superoxide anion generation, thiobarbituric acid reactive substances, myeloperoxidase activity, and reduced glutathione levels were measured to assess oxidative stress in renal tissues. Hematoxylin and eosin stain showed renal histological changes. Results: The significant changes in serum and urinary parameters, elevated oxidative stress, and renal histological changes established the induction of nephrotoxicity. Sinapic acid treatment (20 and 40 mg/kg, orally [p.o.]) provides dose-dependent and significant (P < 0.05) nephroprotection against cisplatin-mediated nephrotoxicity in rats. Nephroprotective effect of sinapic acid was abolished by PPAR-γ inhibitor, bisphenol A diglycidyl ether (30 mg/kg, i.p.) in rats. Conclusion: It is concluded that PPAR-γ agonism serves as one of the mechanisms in sinapic acid-mediated renoprotection.